2010
DOI: 10.1172/jci42273
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acid– and monomethyl fumarate–induced flushing involves GPR109A expressed by keratinocytes and COX-2–dependent prostanoid formation in mice

Abstract: The antidyslipidemic drug nicotinic acid and the antipsoriatic drug monomethyl fumarate induce cutaneous flushing through activation of G protein-coupled receptor 109A (GPR109A). Flushing is a troublesome side effect of nicotinic acid, but may be a direct reflection of the wanted effects of monomethyl fumarate. Here we analyzed the mechanisms underlying GPR109A-mediated flushing and show that both Langerhans cells and keratinocytes express GPR109A in mice. Using cell ablation approaches and transgenic cell typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
173
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(187 citation statements)
references
References 53 publications
5
173
0
1
Order By: Relevance
“…Hca2 À / À , Hca2 mRFP (Gpr109a mRFP ), CD11b-DTR, and Cox1 À / À mice have been reported previously 13,17,21,64 . The Hca2 À / À mice were backcrossed for more than eight generations on a C57BL/6 background; therefore, we used C57BL/6 mice as wild-type controls.…”
Section: Methodsmentioning
confidence: 75%
See 3 more Smart Citations
“…Hca2 À / À , Hca2 mRFP (Gpr109a mRFP ), CD11b-DTR, and Cox1 À / À mice have been reported previously 13,17,21,64 . The Hca2 À / À mice were backcrossed for more than eight generations on a C57BL/6 background; therefore, we used C57BL/6 mice as wild-type controls.…”
Section: Methodsmentioning
confidence: 75%
“…HCA 2 is activated by nicotinic acid, a drug that is used clinically to lower serum lipid concentrations 13 . In doses equal or lower than those used before in mice to exert clinically relevant effects 16,17 , nicotinic acid reduced the infarct size and the ischemic disruption of the blood-brain barrier (Fig. 2a,b).…”
Section: Hca 2 Mediates the Neuroprotective Effect Of Ketogenic Dietmentioning
confidence: 80%
See 2 more Smart Citations
“…Past research has shown that, in particular, the vascular component of flushing is mediated by the hydroxycarboxylic acid receptor 2 (HCA 2 ), also known as G-protein-coupled receptor 109A (GPR109A), expressed in epidermal Langerhans cells and in keratinocytes and directly activated by nicotinic acid. 9 This is based on studies in HCA 2 -deficient mice and on the fact that many synthetic HCA 2 agonists also cause flushing. 8 Interestingly, the active metabolite of dimethyl fumarate, which was recently approved for the treatment of relapsing-remitting multiple sclerosis, 10 is also a HCA 2 agonist and causes flushing as well.…”
mentioning
confidence: 99%